On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA - Calder, Dale R. (Zootaxa, 2019)
Sixty species of hydroids, assigned to 24 families and 39 genera, are recognized and discussed in a collection of material from the southwest coast of Florida. One new species (Clytia joycei) is described from turtlegrass (Thalassia testudinum) and reported as well from the Caribbean coast of Panama. Under provisions of the First Reviser Principle in the International Code of Zoological Nomenclature, Antennopsis nigra Nutting, 1900 is assigned precedence over its simultaneous synonym A. longicorna Nutting, 1900. Also included as a synonym of A. nigra is A. sinuosa Fraser, 1947b. The species is now assigned to Nemertesia Lamouroux, 1816, as N. nigra. Following Reversal of Precedence provisions in the code, the well-known name Halecium nanum Alder, 1859 is designated as valid and conserved as a nomen protectum, while Hydra articulata Bosc, 1797 is relegated to a nomen oblitum. The genus Monotheca Nutting, 1900 is upheld as valid on the basis of both morphological and molecular evidence. Sertularia pourtalesi Nutting, 1904, a seldom-reported species, is assigned to Dynamena Lamouroux, 1812 and recognized as distinct from D. disticha (Bosc, 1802). Calyptospadix cerulea Clarke, 1882 and Bimeria franciscana Torrey, 1902 (also known as Garveia franciscana) are taken to be conspecific, with Calyptospadix Clarke, 1882 treated as a valid genus. Confusion over the identity of Lovenella gracilis Clarke, 1882 in literature on North American hydroids is addressed, and topotypic specimens from the Chesapeake Bay region are illustrated to document characters that distinguish the species. Campanularia colombiana (Wedler, 1976) is reported for the first time outside the Caribbean coast of Colombia. The fauna studied here consists largely of species known to occur in the tropical and subtropical western Atlantic. [Zoobank URL: urn:lsid:zoobank.org:act:4C926BE2-D75D-449A-9EAD-14CADACFFADD]